Distribution and phylogenetic analysis of Dabieshan tick virus in ticks collected from Zhoushan, China - ZHU, Changqiang (J Vet Med Sci, 2020)
Dabieshan tick virus (DBV) belongs to Phlebovirus and its pathogenicity to human and animals is unknown. To investigate the presence of Dabieshan tick virus in Zhoushan, 353 ticks were collected from May 2018 to October 2019. The detection result showed that the average prevalence rate among these samples was 30.3% (107 positives out of 353 samples), which means DBVs are widely distributed in tick populations in Zhoushan of China. In a phylogenetic analysis based on the nucleotide sequences of the L and S segments of the virus (ZS-DBS-2018 tick virus) in the study, it clustered with Dabieshan tick virus (KM817666.1, KM817733.1) with a 97.1% and 99.6% nucleotide identity, respectively. Further studies involving virus isolation are required to characterize Dabieshan tick virus and to expand the geographical distribution of the sampled ticks.